Recent advances in postoperative delirium in elderly patients: pathophysiological mechanisms, risk prediction, and therapeutic strategies - Ding, Xuan-yin; Zhang, Ming-hui; Liu, Jun; Wu, Dan (Frontiers in Neuroscience, 2026)
Postoperative delirium (POD) is a common acute neuropsychiatric syndrome occurring during the perioperative period, characterized by disturbances in consciousness, attention, and cognition. It frequently develops in elderly patients as a consequence of surgery-induced neurofunctional impairment and physiological stress. Clinically, POD manifests with an abrupt onset, fluctuating course, and symptoms such as confusion and disorganized thinking. Multiple predisposing and precipitating factors contribute to its occurrence, including preoperative mental status, general physical condition, diabetes mellitus, electrolyte imbalances, type and duration of surgery, intraoperative blood loss, anesthesia management, and medication use. Understanding the underlying mechanisms of POD in older adults and implementing targeted preventive and therapeutic interventions are crucial for reducing its incidence, enhancing perioperative recovery, and improving the overall safety of surgical care in the elderly population.